Development and validation of a Subjective Post Sleep Diary (SPSD) to assess sleep status in subjects with Restless Legs Syndrome - Calloway, Michael; Bharmal, Murtuza; Hill-Zabala, Christina; Allen, Richard (Sleep medicine, 2011)
To describe the development and psychometric properties of a daily subjective (patient-reported) sleep diary, the Subjective Post Sleep Diary (SPSD), that assesses sleep in relation to Restless Legs Syndrome (RLS). In 2008, the SPSD was developed de novo guided by input from 56 individuals in the US with RLS obtained via focus groups and one-on-one cognitive debriefing sessions. The psychometric properties of the SPSD were evaluated among an additional 470 RLS subjects in the US using three different administration routes; the internet only ( N = 130), an Interactive Voice Response System (IVRS; N = 146) only and a hybrid version (internet and/or IVRS; N = 194). A 12-item sleep diary assessing the key sleep parameters associated with RLS was developed and shown to have face validity following several rounds of focus groups and cognitive debriefing sessions. The SPSD items had high correlations with other sleep instruments and low correlations with constructs unrelated to sleep, and high known-groups predictive ability. The Subjective Post Sleep Diary (SPSD) is a short, valid and responsive instrument for measuring RLS-related sleep via the internet, IVRS or a combination of the two modes for US English speakers.